REFLECTION OF SOCIAL REALITIES IN MUNSHI PREMCHAND’S NOVEL, PRATIGYA - Silpa, Choudhurimayum (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article delves deep into the social realities portrayed in Munshi Premchand’s novels, focusing on themes of dowry, personal sacrifices, marriage and, societal discrimination faced by women, particularly widows in the 1st half of the early 20th century India. The narratives revolve around the lives of characters - Poorna, Kamala Prasad, Dhaannath, etc, and explored the complex social dynamics of early 20th Century rural India. Amritrai is a widower who wanted to change the society by eradicating the social evils happening during his times. He sacrifices his love for Prema and takes on the task of social reform. Prema is a young beautiful woman who embodies the symbol of an ideal woman in traditional society. She is the fiancee of Amritrai. Poorna, a widow, is the heroine of the novel Pratigya. She represents the societal discrimination and social struggles faced by a widow of that time. Dhaannath is a friend of Amritrai. He is a wealthy and influential man who marries Prema. Kamala Prasad is a morally corrupt character and a scheming villain who tries to seduce Poorna.